ANTESEDAN DAN KOSEKUENSI DARI ATTITUDE TERHADAP KOSMETIK HALAL - Elita Mardani; Asep Hermawan (STMIK Widuri Jakarta, 2024)
This research aims to analyze the influence of awareness of halal cosmetics users based on Halal Logo, Halal Brand Image, Halal Awareness, Religiosity, Attitude and Behavioral Intention. Data was obtained through distributing online questionnaires to consumers who use or buy halal cosmetic products. The research sample consisted of 200 respondents selected using purposive sampling techniques. The data analysis method used was Structural Equation Model (SEM) using AMOS 24 software. The results showed that of the nine hypotheses proposed, six hypotheses were accepted and three hypotheses were rejected. The rejected hypothesis is that Halal Logo does not have a positive influence on Attitude, Halal Brand Image does not have a positive influence on Behavioral Intention, and Halal Awareness does not have a positive influence on Behavioral Intention.